THE STATUS OF INTERNATIONAL TREATIES IN THE LEGAL SYSTEM OF THE RUSSIAN FEDERATION: FROM THEORY TO PRACTICE - O. Kiseleva (Правоприменение, 2018)
The subject. The article is devoted to research the legal nature of international treaties.The purpose of the article is to formulate the feasibility of determining the legal status of international treaties in the composition of the sources of law in terms of its unity.The methodology. The author uses the systematic approach to research, methods of anal-ysis and synthesis, including formal legal analysis of international treaties, Russian legislation and courts’ decisions.The main results and scope of their application. The analysis of the categories of legal act, the regulatory agreement, the international treaty, describing its characteristics, legal characteristics is performed. On the basis of the main legal characteristics of the category of normative legal acts, the expediency of inclusion of an international treaty to this category is proven. It is groundless to detach international treaties on normative legal acts, thereby reducing the extent of the need for their application. This, however, does not change the fact that the source of law in each legal system may have special characteristics depending on such system and complementing the basic characteristics. The international treaty is a legal act of international law. Such a conceptual approach to this issue allows making further conclusions.Conclusions. The author highlights the circumstances of the need for reasonable use of international treaties to resolve disputes, that are significant for the process of enforcement. This position is based on the proposed definition of an international treaty including it to the normative legal acts.